An introduction to Islamic literary theory: a conceptual framework for high school students - Fawzia Gilani-Williams (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article is concerned with introducing a new analytical tool for high school students. Islamic literary theory uses an Islamic lens in the study and analysis of literature and cultural productions. It is an empowerment theory that seeks to provide morally-centric emancipatory perspectives grounded in the teachings of the Qur’an and authentic Sunnah. Empowerment theories are concerned with improving the human condition. Islamic literary theory attempts to do this through analyzing texts and discussing Islamic and common sense (fitra) solutions to determine how the human condition can be elevated personally, socially and spiritually. Islamic literary theory uses Islamic principles to critique cultural productions. It seeks to describe and analyze not only the ways in which certain literature reinforces the narrative of secularism and immorality but also how other literature promotes emancipatory and Islamocentric ideas that make the world a better place. It is concerned with exploring how personal, family and micro and macro social life confront problems and achieve transformation through offering insights based on Islam. The Islamic worldview rests on the notion that the individual is in a state of constant struggle from worldly encounters in which s/he must make a choice to act and speak morally and ethically in line with Qur’anic tenets to achieve success in the next life. Islamic literary theory in part critiques how individuals and groups are distracted from their true purpose in life. Texts are analyzed using the Qur’an and authentic hadith to discover in what ways individuals and groups freely, forgetfully or coercively commit wrongs against themselves and others. This paper discusses the emergence of Islamic literary theory as a critical lens for high school students. Furthermore, it discusses its historical foundation and purpose and it provides a conceptual framework for its application.